2019
DOI: 10.1108/et-06-2017-0089
|View full text |Cite
|
Sign up to set email alerts
|

English language and graduate employability

Abstract: Purpose The purpose of this paper is to examine the perspectives of Malaysian employers and students on the need for English language proficiency and skills for employment. Design/methodology/approach Interviews were conducted with employers from various organisations. Additionally, questionnaires were disseminated to undergraduates at four public universities in Malaysia. These were done to ascertain the perspectives of different stakeholders on the importance of English in securing employment, the effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
67
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(72 citation statements)
references
References 18 publications
4
67
0
1
Order By: Relevance
“…The results further reveal that workers can improve their chances of retention and hiring new workers through the timely development of virtual skills, autonomous working and emotional intelligence because individuals who quickly adapt to changing market needs can better capitalize on the positivity of such career shocks [27]. Similarly, effective communication is gaining more significance in the current scenario, and workers who are bilingual and speak any other language fluently have a better chance of job retention or being rehired [28].…”
Section: Discussionmentioning
confidence: 92%
“…The results further reveal that workers can improve their chances of retention and hiring new workers through the timely development of virtual skills, autonomous working and emotional intelligence because individuals who quickly adapt to changing market needs can better capitalize on the positivity of such career shocks [27]. Similarly, effective communication is gaining more significance in the current scenario, and workers who are bilingual and speak any other language fluently have a better chance of job retention or being rehired [28].…”
Section: Discussionmentioning
confidence: 92%
“…Both employers and students agree that English is one of the major determinants of employability. However, despite a consensus between both that good grasp of grammar and extensive vocabulary are significant, the findings in a study by Zainuddin, Pillai, Perlag and Phillip [7] indicated several disparities with regard to students' perceptions and employers' expectations. One of the issues is the blatant use of the colloquial form of English at the workplace which employers found unfavourable.…”
Section: Introductionmentioning
confidence: 92%
“…Table 3 classifies reviewed journal articles by country of origin. Among the 21 journal articles considered in this systematic review, Malaysia had the largest number of published journal articles with a total of 12 studies (Siti Zaidah et al, 2019;Erlane et al, 2018;Shiau et al, 2018;Ting et al, 2017;Rohani et al, 2016;Amar Hisham et al, 2016;Kahirol et al, 2016;Mohd Shamsuri & Izaidin, 2014;Mohd Shamsuri et al, 2013;Sivapalan et al, 2012;Kalaivani et al, 2012;Rahmah et al, 2011). This followed by three studies concentrated on employers' perspective in India (Radhakrishnan & Sudha, 2015;Dhiman, 2012;Wickramasinghe & Perera, 2010), two studies focused on Taiwan employers' perspective (Tsai, 2017;Lin et al, 2010), one study concentrated on employers' perspective in Hong Kong (Pang et al, 2019), one study focused on Israel employers' perspective (Lavy & Rashkovits, 2019), one study concentrated on employers' perspective in Saudi (Khan, 2018) and one study focused on Pakistan employers' perspective (Abbasi et al, 2018).…”
Section: Classifications and Analysesmentioning
confidence: 99%